Review of the monograph by Kolbin A. S., Zyryanov S. K., Belousov D. Yu. "Pharmacovigilance" 2025 - V. I. Petrov (Реальная клиническая практика: данные и доказательства)
The 2nd revised and supplemented edition of “Pharmacovigilance” has been published. This book discusses the drug safety and pharmacovigilance systems from the viewpoint of clinical pharmacology. The history of drug safety studies is given in details. The main definitions and classifications of adverse events are presented below. A separate chapter will examine the pharmacovigilance system in the EAEU member states. The textbook is intended for students, residents, postgraduates, clinical pharmacologists, physicians of other specialties, holders of registration certificates, and researchers.